Characterization of Triterpene Saponin Composition of White, Yellow and Red Beetroot ( Beta vulgaris L.) - Aneta Spórna-Kucab; Anna Tekieli; Krystyna Skalicka-Woźniak; Agnieszka Grzegorczyk; Tomasz Świergosz; Sławomir Wybraniec (Polish Journal of Food and Nutrition Sciences)
Beta vulgaris L. is an important source of bioactive saponins – a group of secondary metabolites – that have spurred a growing interest due to their health-promoting properties. This study aimed to gain information on triterpene saponin profile of the peel and flesh of white, yellow and red beet of six cultivars – Snow Ball, Boldor, Ceryl, Chrobry, Forono and Tytus – harvested in Poland, in the same region. Twenty four saponins with oleanolic acid, hederagenin, akebonoic acid and gypsogenin as aglycons were identified and quantified by liquid chromatography/tandem mass spectrometry (LC-ESI-MS/MS). Among them, betavulgaroside I, II, III and IV were the major compounds, but the quantitative profile of saponins was found to be dependent on beet cultivar and root part, respectively. The highest content of saponins was found in the peel of yellow B. vulgaris Boldor (20812 mg/kg fresh weight, fw), while the lowest saponin content was determined in the flesh of white B. vulgaris Snow Ball (497 mg/kg fw). In addition, the total saponin content in peel and flesh in yellow beet (26054 mg/kg fw) was much higher than the total content in peel and flesh in red beet Tytus (8364 mg/kg fw) and white beet Snow Ball (1204 mg/kg fw). This is the first report on the profile of saponins in white and yellow beets.